Why do they leave? Examining dropout behaviour in gender-atypical vocational education and training in Germany - Beckmann, Janina [Verfasser] (My University, 2023)
„Germany’s VET system is highly gender-segregated and marked by high dropout rates. This article investigates the dropout behaviour of apprentices in gender-atypical training occupations. First, we investigate whether gender-atypical apprentices drop out at a higher rate than their majority peers. Second, we examine differences in the self-reported reasons for dropping out among gender-typical and gender atypical apprentices. Results show that gender-atypical apprentices, and particularly males in female-dominated occupations, are more likely to prematurely leave their apprenticeship. The self-reported reasons for dropping out differed by gender minority status: female minorities were more likely to drop out due to a lack of social integration, while male minorities were more likely to drop out due to unfulfilled aspirations in comparison to the gender majority. These results show that gender-specific perceptions and experiences are related to the higher dropout rates of gender-atypical apprentices.“ (author’s abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); 370; 300; Berufsausbildung; Ausbildungsstellenmarkt; Ausbildungsabbruch; Einflussfaktor; geschlechtsspezifische Faktoren; geschlechtsspezifische Faktoren; Frauenberuf; soziale Integration